2020
DOI: 10.21037/atm-20-5100
|View full text |Cite|
|
Sign up to set email alerts
|

Using a deep recurrent neural network with EEG signal to detect Parkinson’s disease

Abstract: Background: Parkinson's disease (PD) gradually degrades the functionality of the brain. Because of its relevance to the abnormality of the brain, electroencephalogram (EEG) signal is used for the early detection of this disease. This paper introduces a novel computer-aided diagnosis method to detect PD, which is an efficient deep learning method based on a pooling-based deep recurrent neural network (PDRNN). Therefore, the purpose of this study is to detect Parkinson's disease based on deep recurrent neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Around half of the included studies used convolution neural networks ( n = 37); afterward, other neural networks ( n = 31) were implemented in the included studies, followed by artificial neural networks (ANNs) ( n = 10), recurrent neural networks (RNNs) ( n = 9), and fuzzy neural networks (FNNs), as shown in Table 3 . In the end, the most imitated neural network architecture in the included studies was LSTM ( n = 11) [ 6 , 34 , 36 , 38 , 40 , 65 , 70 , 74 , 77 , 80 , 83 ], VGG ( n = 3) [ 18 , 27 , 58 ], and DNN ( n = 6) [ 34 , 35 , 60 , 91 , 92 , 103 ]. Recently, with the developments of new techniques such as convolutional neural network [ 101 ] and transfer learning [ 63 ], deep learning gained significant advances in the computer vision tasks, e.g., ImageNet [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around half of the included studies used convolution neural networks ( n = 37); afterward, other neural networks ( n = 31) were implemented in the included studies, followed by artificial neural networks (ANNs) ( n = 10), recurrent neural networks (RNNs) ( n = 9), and fuzzy neural networks (FNNs), as shown in Table 3 . In the end, the most imitated neural network architecture in the included studies was LSTM ( n = 11) [ 6 , 34 , 36 , 38 , 40 , 65 , 70 , 74 , 77 , 80 , 83 ], VGG ( n = 3) [ 18 , 27 , 58 ], and DNN ( n = 6) [ 34 , 35 , 60 , 91 , 92 , 103 ]. Recently, with the developments of new techniques such as convolutional neural network [ 101 ] and transfer learning [ 63 ], deep learning gained significant advances in the computer vision tasks, e.g., ImageNet [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…In [ 38 , 83 ], we found that long short-term memory (LSTM) achieved outstanding results, indicating the best option to deal with EEG data. On the other hand, seven studies [ 3 , 19 , 25 , 27 , 40 , 69 , 101 , 102 ] focused on the classification of handwriting image to identify PD in the early stage, and we found that outstanding results were achieved in ANN + SVM in [ 3 ], dual-path RNN (DPRNN) in [ 40 ], and CNN + Optimum-Path Forest (OPF) in [ 102 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…AEN posed outstanding scores in terms of all performance metrics, leading to a conclusion that AEN is potential of detecting AD. In [170], the authors claimed that pooling based deep RNN on EEG signals to detect PD was investigated for the first time. The results of the study proved the model's compatibility in terms of PD detection.…”
Section: ) Ml-based Approaches In Pd Diagnosismentioning
confidence: 99%
“…Deep learning models have been applied to PD EEG to perform a range of tasks such as discriminating on-medication from offmedication conditions (Shah et al, 2020) and classification between PD and healthy controls (HC) based on EEG collected during a specific task (Shi et al, 2019). However, there are only three studies (Lee et al, 2019a;Oh et al, 2018;Xu et al, 2020) that have deployed deep learning to discriminate between PD and HC using resting-state EEG. In (Oh et al, 2018), a thirteen-layer convolutional neural network (CNN) structure was proposed, which achieved 88.3% accuracy, 84.7% sensitivity, and 91.8% specificity using raw resting EEG data collected from 20 PD and 20 HC.…”
Section: Introductionmentioning
confidence: 99%